Persaingan Vs Kerjasama Industri dalam Perspektif Islam - Manzilati, Asfi; Wildana, Muhammad Dandy Alif; Syamsuri, Asyila Muthi'ah; Nabila, Ulfa (Jurnal Pendidikan Ekonomi Undiksha, 2024)
Industry is one of the main driving forces in the economy, this can be proven from economic data which shows the contribution of industry to economic growth. However, if we look further, the industries that existed at this time were concentrated in certain parties, giving rise to inequality, both in terms of ownership structure and the resulting economic impacts. Therefore, alternatives are needed to answer the phenomenon of industrial concentration that is occurring today. This research aims to offer a concept that can break down the concentration of control of certain parties in an industry so that there is equality in ownership and access to economic resources.